The State of Working America, 2006/2007 - Russell, Jason (Labour / Le Travail, 2008)
The article reviews the book, "The State of Working America 2006/2007," by Lawrence Mishel, Jared Bernstein and Sylvia Allegretto.
Keywords: ALLEGRETTO; Sylvia; BERNSTEIN; Jared; BOOKS – Reviews; Labor; MISHEL; Lawrence; Nonfiction; STATE of Working America 2006-2007; The (Book)